Stabilization of power system using improved virtual inertia of virtual synchronous generator - Poungdokmai, Aditap; Polmai, Sompob (My University, 2022)
The renewable energy source (RES) based distributed generation (DG) has grown up rapidly that causing a reduction inertia and instability of power system. To support the increased RES, grid connected inverters require improved control schemes. Therefore, Virtual synchronous generator is getting attention. VSG is a control scheme applied for distributed generating (DG) that controls virtual rotational synchronous generator and enhances stability of power system. However, VSG has some issues when grid frequency fluctuations occur, which can cause the steady-state active power output deviation. It can be solved by analyzing closed loop transfer function of power output. The steady-state power deviation is caused by damping coefficient in the swing equation of the VSG. Thus, power deviation is decreased by set damping coefficients to zero and adding differential compensation to control dynamic characteristic instead of damping coefficients. By adding differential compensation, we can control dynamic characteristics without steady-state power output deviation in weak grid.
Keywords: and grid frequency fluctuate; grid weakening; power deviation; Virtual inertia; Virtual synchronous generator (VSG)